Complications of Menstrual Regulation in a Tertiary Care Hospital in Dhaka city of Bangladesh: A Cross Sectional Study (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Menstrual regulation is an alternate important way of reproductive life of females.Objective: The purpose of this present study was to find out the outcomes of complications of menstrual regulation. Methodology: This observational cross-sectional study was conducted on 384 unsafe MR cases were included in this study in the Department of Obstetrics and Gynecology, Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh, over the period of 12 (twelve) months, dated from January 2011 to December 2011.A data collection sheet was formed which included all the parameters and variables of interests. After selection, eligible women were informed about the study and a written consent was taken. In this observational study all women were to be interviewed, their detail history, findings of physical examination and investigation reports were checked and the information’s were recorded in the data collection form.Results: The age of the patients ranged from 16 to 40 years and most of the patients belonged to ’26 to 30 years’ age group is 31.8%. The mean duration of stay was 7.32 days and the total duration ranged from 1 to 28 days. In spite of the large range of stay, more than half 53.3% of the respondents were released from the hospital within 3 days. In this study shows that the respondents were having various difficulties following abortion induction; most of them were suffering from abdominal pain was the most prevailing condition [358 (93.2%)] followed by per vaginal bleeding 90.1%. The complications of the patients developed following unsafe abortion. The most complications found Four-fifth of the cases 80.2% were found with retained product of conception. More than one-fifth were in shock 21.6%and another one-fifth were suffering from per vaginal bleeding 20.0%.Conclusion: Menstrual Regulation happens mostly in unsafe abortion leading to comorbidity of life even death.Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):64-69